2001
DOI: 10.1073/pnas.191368398
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized xenon as a biosensor

Abstract: The detection of biological molecules and their interactions is a significant component of modern biomedical research. In current biosensor technologies, simultaneous detection is limited to a small number of analytes by the spectral overlap of their signals. We have developed an NMR-based xenon biosensor that capitalizes on the enhanced signal-to-noise, spectral simplicity, and chemical-shift sensitivity of laser-polarized xenon to detect specific biomolecules at the level of tens of nanomoles. We present res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
327
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 306 publications
(335 citation statements)
references
References 28 publications
5
327
0
3
Order By: Relevance
“…51 We have now extended the experiments to a complete titration of the free biosensor with avidin ( Figure 4) showing that increasing amounts of avidin lead to corresponding …”
Section: Titration Of Biotinylated Functionalized-xenon Biosensor Witmentioning
confidence: 91%
See 3 more Smart Citations
“…51 We have now extended the experiments to a complete titration of the free biosensor with avidin ( Figure 4) showing that increasing amounts of avidin lead to corresponding …”
Section: Titration Of Biotinylated Functionalized-xenon Biosensor Witmentioning
confidence: 91%
“…[60][61][62][63] Previous experimental studies, which are now being understood with theoretical models by Sears and Jameson, 64 have shown that direct changes to the basic structure of the cryptophane-A cage perturb the chemical shift of the cryptophane-encapsulated xenon. For example, a 30 ppm change in chemical shift was noted when the length of the bridges between the cyclotriveratrylene caps of cryptophane-A was increased by one methylene group, 51 and even deuteration of a single methoxy group on a cryptophane-A cage has been shown to produce a noticeable shift (~0.1 ppm). 65 In this work, we show that significant xenon chemical shift differences also result from derivatizations of cryptophane-A that are not local to the encapsulated xenon.…”
Section: Biosensor Molecule Diastereomers Detected By Functionalized mentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the use of low-bandwidth pulses is an important step for reading out different sensor signals in the same system (multiplexing, (7,10)). …”
mentioning
confidence: 99%